2020
DOI: 10.3390/ijms21176324
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Escherichia coli Expression System in Producing Antibody Recombinant Fragments

Abstract: Antibodies and antibody-derived molecules are continuously developed as both therapeutic agents and key reagents for advanced diagnostic investigations. Their application in these fields has indeed greatly expanded the demand of these molecules and the need for their production in high yield and purity. While full-length antibodies require mammalian expression systems due to the occurrence of functionally and structurally important glycosylations, most antibody fragments and antibody-like molecules are non-gly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(62 citation statements)
references
References 244 publications
(280 reference statements)
0
62
0
Order By: Relevance
“…bACE2-Rm contains six potential N-linked glycosylation sites (N53, N90, N329, N546, N660, and N690), and the structure of hACE2 has been revealed to be highly glycosylated ( 19 , 20 ). A previous study has reported that the glycosylation of proteins varies in different expression systems ( 21 ); for example, proteins are nonglycosylated in Escherichia coli -based expression platforms ( 22 ). The glycosylation compositions of proteins are substantially different when expressed in HEK293T cells and insect cells ( 23 , 24 ).…”
Section: Resultsmentioning
confidence: 99%
“…bACE2-Rm contains six potential N-linked glycosylation sites (N53, N90, N329, N546, N660, and N690), and the structure of hACE2 has been revealed to be highly glycosylated ( 19 , 20 ). A previous study has reported that the glycosylation of proteins varies in different expression systems ( 21 ); for example, proteins are nonglycosylated in Escherichia coli -based expression platforms ( 22 ). The glycosylation compositions of proteins are substantially different when expressed in HEK293T cells and insect cells ( 23 , 24 ).…”
Section: Resultsmentioning
confidence: 99%
“…After the appropriate genetic engineering and the introduction of the desired construct encoding for the protein in the selected E. coli strain, the process development starts in general by small-scale cultures for the screening of expression conditions using initially Petri plates and then small volume shake flasks, i.e., 10 of mL to a few liters. Various cultivation parameters, such as media composition, pH, agitation, aeration, temperature, cell density, type and concentration of inducers, induction time, and other strategies affect the protein expression levels depending upon the expression system [9]. All these will be discussed in detail in the forthcoming sections and are summarized in Table 1 that is a synopsis of the literature about the expression of antibodies and their fragments in E. coli.…”
Section: -Cultivation Conditionsmentioning
confidence: 99%
“…These antibody fragments, especially Fab, are popular formats of antibodies, due to their excellent thermostability, proven clinical safety, and their ease of production in the microbial system [15]. The Fab fragment is a heterodimeric and monovalent antibody fragment (50 kDa) composed of an antibody light chain (VL ĂŸ CL domains) linked by a disulfide bond to the antibody heavy chain (VH ĂŸ CH1 domains) [9]. Disulfide bonds are the most common post-translational modifications found in many proteins that stabilize their tertiary and quaternary structures.…”
Section: Recombinant Antibody Structure Importance and Heterologous Expressionmentioning
confidence: 99%
“…Periplasmic expression of recombinant proteins in E. coli has been investigated extensively in the past decades ( Zhou et al, 2018 ; Sandomenico et al, 2020 ). The oxidative environment of the periplasm favors correct folding of proteins containing disulfide bridges and generally enhances solubility and stability of the product ( Sandomenico et al, 2020 ). Translocation through the inner membrane is achieved by adding signal sequences initiating specific transport pathways to the product.…”
Section: Introductionmentioning
confidence: 99%